CBMT-09. ESTABLISHMENT AND IN VITRO CHARACTERIZATION OF A SPORADIC PEDIATRIC ATYPICAL MENINGIOMA CELL LINE. (5th November 2018) - Brown, Desmond; Kaptzan, Tatiana; Peterson, Timothy; Jentoft, Mark; Daniels, David
Abstract: Meningiomas represent ~30% of primary neoplasms in adults but only 0.4–4.6% in children. Due to the paucity of cases, relatively few studies have addressed pediatric meningiomas and there are insufficient cell lines to conduct in vitro studies. We have established and characterized a new cell line (PED-24) from a 12-year-old male who presented with headaches and subsequently underwent gross total resection of a sporadic, large left frontal meningioma, WHO grade 2. The tumor was focally positive for EMA and GFAP. Whole-exome sequencing of the patient was negative for NF-2. Compared to three high grade glioma lines (two H3K27M DIPG tumors and one adult GBM), PED-24 showed significantly increased growth kinetics as assessed by real-time live-cell analysis. The cells were also successfully cultured as neurospheres in neurobasal medium. Ultrastructural analysis with SEM and TEM demonstrated unique cellular morphology. Average cellular diameter was 3.2 ± 0.3 µm and the cells had a microvilli-covered smooth surface. There was a high burden of transport vesicles and an extensive network of endoplasmic reticulum with evidence of autophagy events. This line provides a resource for further exploration of pathogenic mechanisms involved in sporadic pediatric meningiomas. One novel avenue of interest is the potential presence of a stem-like subpopulation within sporadic pediatric atypical meningiomas.